Continuous response despite reduced dose of trametinib as single agent in an adolescent with a relapsed disseminated pediatric low-grade glioma KIAA1549-BRAF fusion positive: a case report and review of the literature - Castellano-Damaso, Serafin; Vazquez-Gomez, Felisa; Moreno-Carrasco, Jose Luis; Arce, Begoña; Borrego, Pedro; Lassaletta, Alvaro (Frontiers in Oncology, 2024)
Dissemination in pediatric low-grade glioma may occur in about 4-10% of patients according to retrospective cohort studies. Due to its low incidence, there is no consensus on treatment for these patients. According to the constitutional activation of the MAPK/ERK pathway in these tumors, MEK inhibitors such as trametinib have been used successfully in the relapsed setting. Skin toxicity is frequent in patients receiving trametinib, normally mild to moderate, but sometimes severe, needing to discontinue the drug, limiting the efficacy in the tumor. There is not much information in the literature regarding whether reducing the dose of trametinib is able to maintain efficacy, while at the same time decreasing toxicity. Here we present an adolescent, with severe skin toxicity, whose trametinib dose was reduced by 50%, and efficacy on the tumor continued while skin toxicity significantly decreased.